Pengembangan Multimedia Pembelajaran “Scraperat” Untuk Meningkatkan Kemampuan Penalaran Matematis Siswa Kelas IX - Yulhana Faradilla; Megita Dwi Pamungkas; Fadhilah Rahmawati (RANGE: Jurnal Pendidikan Matematika, 2023)
Technology has a big role in education. Education is required to be able to keep abreast of technological developments. In this case, teachers must be able to apply technology-based learning, one of which is in learning mathematics. The findings from the observations also show that the mathematical reasoning abilities of class IX A students at SMP Negeri 1 Mertoyudan are still in the low category. Therefore, innovation is needed in learning, one of which is using technology in learning. The effort that can be done is to develop a multimedia Scraperat to improve students' mathematical reasoning abilities. This type of research is research and development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). the conclusion obtained is that multimedia learning scraperat to improve students' mathematical reasoning abilities is stated to be valid, practical, and effective. Advice for readers is to always be motivated to provide products that can improve the quality of learning and education.